Adjusting to austerity: the public spending responses of regional governments to the budget constraint in Spain and Italy. (19th September 2021) - Toubeau, Simon; Vampa, Davide
Abstract: What are the effects of fiscal imbalances, and austerity, on regional-level spending? To answer this question, we examine an original dataset of yearly spending decisions of regional governments in Italy and Spain between 2003 and 2015. We find that the rise in regional deficits has an important negative effect on regional governments' spending. The strength of this effect is, however, mitigated by the presence of a left-wing party in regional office. In addition, we uncover an important variation in the extent of cutbacks across policy sectors: regional governments tend to protect the health sector and focus their retrenchment efforts on social assistance and running of public institutions. Partisanship matters here too, as left-wing parties tend to protect healthcare more than their right-wing rivals. These findings bear relevance for understanding the role of partisanship and policy sector in the process of public retrenchment in multi-level states.